The Role of Innovation Capability in the Relationship Between Social Capital, Entrepreneurial Leadership and MSME Performance in Semarang’s Culinary Sector - Annur, Abdul Fattah; Wartini, Sri; Martono, S; Soliha, Euis (Universitas Negeri Semarang, 2025)
This study examines the effect of social capital and entrepreneurial leadership on the performance of MSMEs with innovation capability as a mediating variable. The population of this study was culinary sector MSMEs in Semarang City, with a sample of 193 respondents determined by Taro Yamane formula. Data analysis techniques include validity and reliability tests, descriptive analysis, and hypothesis testing using the Structural Equation Modeling (SEM) through SmartPLS version 4.0. The results show that social capital and entrepreneurial leadership have a positive effect on innovation capability and MSME performance. This finding confirms the role of innovation capability as a mediating variable that strengthens the relationship between social capital and entrepreneurial leadership on MSME performance. For further research, it is recommended to include other variables such as market orientation and different leadership styles in order to expand the conceptual model developed.